Study Komparatif Konsep Perdamaian dalam Al-Qur’an dan Bible - Devi kusumawati (Al-Ahnaf: Journal of Islamic Education, Learning and Religious Studies, 2025)
This study discusses a comparative analysis between the Qur’an and the Bible regarding the concept of peace, as both religions consistently teach their followers to live in harmony, including in Islam and Christianity. Peace refers to a state in which there is no hostility, no conflict, and no war. The research method used in this article is a qualitative comparative method with a descriptive-analytical approach, by analyzing (describing) and comparing the concept of peace in the Qur’an and the Bible. The aim of this study is none other than to provide an interfaith perspective that can strengthen the foundation for interreligious dialogue. The results of this study reveal a comparison between the Qur’an and the Bible, in which both scriptures promote peace among their followers through the prohibition of violence, the emphasis on justice, and the encouragement of peace through freedom. The differences in the concept of peace between the Qur’an and the Bible include: in matters related to divinity, the Qur’an emphasizes peace through submission to Allah and obedience, whereas the Bible highlights peace through the reconciliation of sin by Jesus Christ. The Qur’an forbids violence but permits defensive war, while the New Testament teaches love and rejects physical violence. Despite these differences, both scriptures support the idea of universal peace.